2016
DOI: 10.5152/tjbh.2016.2753
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment Approach and Social Support Needs for Patients with Breast Cancer

Abstract: IntroductionBreast cancer is the second most common cancer type in the world and the most common cancer type in women. The number of newly diagnosed breast cancers in 2012 was 1.67 million, and breast cancer makes up 25% of all types of cancer in women (1). According to the data of the World Health Organization (WHO), the number of women who died of breast cancer worldwide in 2011 was 508 000. Breast cancer incidence increases as life expectancy increases, and urbanization and western lifestyles are adopted mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In the present study, it was determined that the perceived social support from family and total perceived social support were associated with effective coping with stress. In the literature, social support was found useful for patients with cancer, and these patients often received support from their families . It was determined that the support received from family members had a positive correlation with well‐being of patients with cancer, and as the support received from family increased, effective coping ways increased .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, it was determined that the perceived social support from family and total perceived social support were associated with effective coping with stress. In the literature, social support was found useful for patients with cancer, and these patients often received support from their families . It was determined that the support received from family members had a positive correlation with well‐being of patients with cancer, and as the support received from family increased, effective coping ways increased .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, social support was found useful for patients with cancer, 19,[22][23][24] and these patients often received support from their families. 5,17,20,24,33 It was determined that the support received from family members had a positive correlation with well-being of patients with cancer, 19,22,23 and as the support received from family increased, effective coping ways increased. 5,17,33 It was also reported that as the perceived social support increased, effective coping with stress increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were asked questions that involved breast self-examination, Pap smear test, clinical breast examination, diet, smoking and age at first labour. The findings are presented in detail in the tables in the findings section (Göl & Erkin, 2016;İz & Tümer, 2016;Kanbur & Çapık, 2011;Kolutek & Avci, 2015;Kurt, Canbulat, & Savaşer, 2013;Soylar & Genç, 2016).…”
Section: Surveymentioning
confidence: 99%
“…Increasing prevalence of cancer every day is an important public health problem both in Turkey and in the world. If the cancer increase rate continues this way by the year 2030, every year 27 million new cancer diagnosis will be made, every year 17 million people will lose their lives due to cancer, and the number of people living with cancer will reach up to 75 million (Güner & Taşkıran, ; Kolutek & Avci, ; Soylar & Genç, ). International Agency for Research on Cancer (GLOBOCAN) data show that 14.1 cancer cases have developed worldwide, and there have been 8.2 million cancer‐related deaths (Carter, ).…”
Section: Introductionmentioning
confidence: 99%